توظيف النص الشعري في تطوير العناصر و المهارات اللغوية للناطقين بغير العربية الشعر الحديث نموذجاً - بن ندا العتيبي, بدر (Revues faculté des lettres et des langues; No 17 (2015): مجلة كلية الآداب واللغات)
تحاول هذه الدراسة الاقتراب من عملية تدريس النص الشعري لمتعلم اللغة العربية من غير الناطق بها، وهو أمر  من أهم محاور التعليميات المعاصرة، لما لهذه العملية من دور في تطوير استراتيجية التعلم والتعليم في مختلف مجالات الاختصاص. ومنه، نحاول إعداد منهج علمي يروم الجدة والدقة في دراسة النص الشعري الحديث وتدريسه للناطق بغير العربية. والهدف من المحاولة، هو بيان مدى الإفادة من تدريس الشعر العربي الحديث على الخصوص في تعليم اللغة العربية لهذه الفئة؛ لنعالج بذلك موضوع  توظيف النص الشعري في تطوير  العناصر و المهارات اللغوية  للناطق بغير العربية.  The current paper undertakes to approach the teaching of Arabic poetic texts to non-native speakers (NNS)  of Arabic (i.e., speakers of languages other than Arabic). The topic itself evolves around the realm of Didactics of Arabic Language   (DAL). It is within the range of the paper to aim to contribute to the development of the teaching-learning process in a wide pethora of other disciplines. In fact, the intention is on establishing a scientific approach to the teaching of Arabic poetic texts to learners whose L1 is other than Arabic, and who are suspected to encounter immense challenges in learning the texts in question. The goal of such an endeavor is to provide the targeted learners population (namely, non-speakers of Arabic)  with the necessary skills to appreciate the study of modern Arabic poetic texts.